2022
DOI: 10.1287/orsc.2021.1453
|View full text |Cite
|
Sign up to set email alerts
|

Misaligned Meaning: Couples’ Work-Orientation Incongruence and Their Work Outcomes

Abstract: This research investigates the relationship between couples’ work-orientation incongruence—the degree to which romantic partners view the meaning of their own work differently—and their ability to succeed in making job transitions and experiencing satisfaction with the jobs they hold. We use a social information-processing approach to develop arguments that romantic partners serve as powerful social referents in the domain of work. By cueing social information regarding the salience and value of different aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 113 publications
0
6
0
Order By: Relevance
“…However, little research has examined how the meaning that people perceive in their work relates to their responses to the potential challenges of occupational destabilization. Research on job loss and involuntary role exits has generally not examined the role of work meanings in these experiences (Kanfer, Wanberg, and Kantrowitz, 2001; McKee-Ryan et al, 2005; Wanberg, Zhu, and Van Hooft, 2010; but see Kaufman, 1982; Wrzesniewski, 1999; and Jiang and Wrzesniewski, 2022 for exceptions). This is a critical omission, as several studies have suggested that the meaning of work matters for one’s experience after job loss.…”
Section: Navigating Occupational Destabilization: Job Loss and Involu...mentioning
confidence: 99%
“…However, little research has examined how the meaning that people perceive in their work relates to their responses to the potential challenges of occupational destabilization. Research on job loss and involuntary role exits has generally not examined the role of work meanings in these experiences (Kanfer, Wanberg, and Kantrowitz, 2001; McKee-Ryan et al, 2005; Wanberg, Zhu, and Van Hooft, 2010; but see Kaufman, 1982; Wrzesniewski, 1999; and Jiang and Wrzesniewski, 2022 for exceptions). This is a critical omission, as several studies have suggested that the meaning of work matters for one’s experience after job loss.…”
Section: Navigating Occupational Destabilization: Job Loss and Involu...mentioning
confidence: 99%
“…A longitudinal study encompassing couples in which one was employed and the other was unemployed has shown that a high level of incongruence in work orientation be-tween couples was associated with poor job satisfaction for employed partners over time (Jiang & Wrzesniewski, 2022).…”
Section: Work Orientationmentioning
confidence: 99%
“…Understanding how various organizational stakeholders interpret meaning and associate value to various organizational initiatives is critical to understanding organizational life Meaning and willingness to pay (Jiang and Wrzesniewski, 2021). In this respect, one of the earliest theories explaining how consumers make consumption decisions and value different product bundles is the theory of consumer choice in microeconomics.…”
Section: Theory Of Consumer Choicementioning
confidence: 99%
“…Meaning in organizational life (Jiang and Wrzesniewski, 2021) has important implications for how organizational stakeholders associate value to various organizational initiatives (Zeglat and Janbeik, 2019; Rosso et al , 2010; Ariely et al , 2008). In particular, research on meaning has generally shown that effort increases favorable valuation of and WTP for economic activities (Kim and Tanford, 2019; Pickup et al , 2019; Tatavarthy and Mukherjee, 2019; Norton et al , 2012; Lydall et al , 2010; Alessandri et al , 2008).…”
Section: Contributions and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation